Penggunaan Media Audio Visual dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran IPAS Kelas V Sekolah Dasar Negeri 002/IX Sekernan Muaro Jambi - Mita Afrianti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to determine the effect of using audio-visual media in increasing students' interest in learning. Class V at SDN 002/IX Sekernan. The method used was classroom action research with two cycles, which involved observation and questionnaires to measure changes in students' interest in learning. questionnaires to measure changes in students' interest in learning. Data were analyzed using quantitative and qualitative descriptive statistical techniques, with focus on increasing student engagement and attention during the learning process. learning process. The results showed that the application of audio-visual media significantly increased students' interest in learning, with the percentage of interest increasing from 56.1% in cycle I to 80.25% in cycle II. increased from 56.1% in cycle I to 80.25% in cycle II. The increase This increase shows that audio-visual media is effective in creating a more interesting and enjoyable learning atmosphere. learning atmosphere that is more interesting and enjoyable, so that it can increase student students' participation and understanding of the subject matter. This research confirms that audio-visual media is one of the solutions to improve students' interest and learning outcomes significantly